Incidence of Malignancy in Solitary Thyroid Nodule and Multinodular Goiter Post-Thyroidectomy - Alhatemi, Murtadha Moojid Hadi; Smaysim, Ali Liwaa Abdulsahib; Alshabeeb, Ahmed Abdulbari Neamah (Open Journal of Physicians and Surgeons, 2025)
Background: Thyroid malignancy has varied prevalence worldwide, it’s believed that multinodular goiter (MNG) is associated with a lower risk of malignancy compared to solitary thyroid nodules (STN). Aim of Study: The study aims to determine the incidence of malignancy in multinodular goiter (MNG) versus solitary thyroid nodule (STN) and the sub-types of malignant condition in a series of Iraqi patients with goiter. Patients and methods: The study was carried out in the department of general surgery in Alsader medical city in al Najaf city by taking the histopathological reports of 181 patients who underwent thyroidectomy over 1-year. Histopathological analysis reports were divided in to two groups first was 140 surgically resected thyroidectomy specimens of multinodular goiter and the second was 41 cases of solitary thyroid nodule to determine the incidence and the types of malignancy in each group. Results: Out of the 140 MNG cases and the 41 STN cases, malignancy reported in 29 (20.7%) and 18 (43.9%), respectively, (P. value<0.05). Papillary thyroid carcinoma was the commonest malignancy observed in both groups. Conclusions: Thyroid cancer was significantly less frequent in multinodular goiter as compared with single nodule. Follicular thyroid carcinoma is more frequent in STN as compared to MNG. Male gender and age were considered as a risk factor for malignancy